Can Omitted Carbon Abatement Explain Productivity Stagnation? - Dai, Sheng; Kuosmanen, Timo; Zhou, Xun (Wiley, 2025)
Explaining the secular stagnation of productivity growth is a widely recognized challenge to economists and policymakers. One potentially important explanation without much attention concerns the ongoing low-carbon transition. This paper explores whether considering greenhouse gas emissions can explain productivity stagnation in OECD countries. We propose a quantile shadow-price Fisher index to gauge green total factor productivity (TFP) based on the newly developed penalized convex quantile regression approach. The quantile shadow-price Fisher index requires neither the real price data nor an ad hoc choice of quantiles and allows the quantiles to move in the inter-period sample. An empirical application to 38 OECD countries during 1990-2019 demonstrates that the measured productivity growth is considerably higher when the GHG emissions are accounted for. For countries that have reduced GHG emissions most actively, the average green TFP growth rate could double the conventional TFP growth. The impacts of ignoring human capital and different representations of fixed capital on green TFP growth are also discussed explicitly.